All Staphylococcus aureus bacteraemia-inducing strains can cause infective endocarditis: Results of GWAS and experimental animal studies. Issue 2 (February 2023) - Bastien, Sylvère; Meyers, Severien; Salgado-Pabón, Wilmara; Giulieri, Stefano G.; Rasigade, Jean-Phillipe; Liesenborghs, Laurens; Kinney, Kyle J.; Couzon, Florence; Martins-Simoes, Patricia; Moing, Vincent Le; Duval, Xavier; Holmes, Natasha E; et al.
Highlights: Staphylococcus aureus bacteraemia (SAB) can lead to infective endocarditis (IE). Specific traits of IE-causing strains versus SAB-only are questioned. GWAS from IE and SAB-only strains does not discriminate the 2 groups. In murine and rabbit IE models, IE and SAB-only strains behave in the same way. Summary: Objectives: We aimed at determining whether specific S. aureus strains cause infective endocarditis (IE) in the course of Staphylococcus aureus bacteraemia (SAB). Methods: A genome-wide association study (GWAS) including 924 S. aureus genomes from IE (274) and non-IE (650) SAB patients from international cohorts was conducted, and a subset of strains was tested with two experimental animal models of IE, one investigating the early step of bacterial adhesion to inflamed mice valves, the second evaluating the local and systemic developmental process of IE on mechanically-damaged rabbit valves. Results: The genetic profile of S. aureus IE and non-IE SAB strains did not differ when considering single nucleotide polymorphisms, coding sequences, and k-mers analysed in GWAS. In the murine inflammation-induced IE model, no difference was observed between IE and non-IE SAB strains both in terms of adhesion to the cardiac valves and in the propensity to cause IE; in the mechanical IE-induced rabbit model, there was no difference between IE and non-IE SAB strains regarding the vegetation size and CFU. Conclusion: All strains of S. aureus isolated from SAB patients must be considered as capable of causing this common and lethal infection once they have accessed the bloodstream.